AHP Analyser: A decision-making tool for prioritizing climate change mitigation options and forest management - Soam, Sudhir Kumar; N, Srinivasa Rao; BS, Yashavanth; Balasani, Raghupathi; S, Rakesh; Marwaha, Sudeep; Kumar, Prabhat; Agrawal, R. C. (Frontiers in Environmental Science, 2023)
Agricultural and Forest Research and Environmental Management entail significant decisions that can impact research findings. Better findings come from well-managed research. In the research and management, a practical methodology approach is used to improve decision-making and prioritise numerous possibilities and research programmes. However, most research scientists need help setting the priority for the research project. A web-based decision-making system, i.e., the Analytical Hierarchy Process (AHP) methodology, provides support and solutions in prioritising the research project options based on multi-criteria decisions in order to eliminate these barriers in agricultural research and management. Considering these factors, the National Academy of Agricultural Research Management (NAARM), Hyderabad, Telangana, India, devised and developed "AHP Analyser", a web-based group decision-making tool for prioritising the climate change mitigation options of research projects using an analytical hierarchy approach. It was created with PHP, JavaScript, and MySQL and is available at https://naarm.org.in/ahp/. In the present is research article, we have briefly discussed the AHP methodology, analytics of publication on AHP usage, primary features of the AHP Analyser, which was built by using AHP methodology, and a case study that shows how the AHP Analyser was used to mitigate climate change in the forestry sector. Study concluded that AHP methodology can be widely applicable in various sectors for decision making, portfolio management and prioritisation; also contributes to the sustainable development goals (SDGs). Therefore, creating awareness on the advantages of AHP methodology among the researchers is critical to bring quality outputs in the research field.